Old age poverty - Gerdina, Otto (Annales. Series historia et sociologia, 2025)
This article examines gender differences in old-age poverty in Slovenia through a life course perspective. Using qualitative in-depth interviews with 33 individuals aged 65 and older, the article identifies gender specific patterns of deprivation. Findings reveal that both men and women experience fragmented work histories and engagement in the grey economy, but women face additional disadvantages due to lower education levels, caregiving responsibilities, and persistent gender pay gaps. The insight into the interplay between structural inequalities and individual trajectories in shaping old-age poverty contributes to an understanding of the ways in which gender specific disadvantages accumulate over time.
Keywords: razlike med spoloma; revščina; Slovenija; socializem; starost; strukturne neenakosti; življenjski potek